PENGEMBANGAN GAME ADVENTURE TEKNODIGITALIN PADA MATA PELAJARAN INFORMATIKA KELAS SMA/SEDERAJAT - Maisyarah; Meldi Ade Kurnia Yusri; Nofri Hendri; Khairul Alfahani (STKIP Subang, 2026)
The development of this adventure game was undertaken to address challenges in the computer science curriculum, specifically the limited diversity of teaching materials, which often diminishes students' interest in learning and hinders their understanding without visual examples. This study aims to create a valid and practical adventure game for tenth-grade high school students or equivalent levels. The research employed a Research and Development (R&D) methodology using the 4D development model—Define, Design, Develop, Disseminate. Validity testing was conducted by three experts: one content validator and two media validators. Practicality testing involved tenth-grade students, followed by dissemination and effectiveness evaluation with computer science teachers and tenth-grade students at two different schools. The validity assessment conducted by subject matter experts yielded a 93.7% score, classified as very valid. The combined validity assessment results from Media Expert I and Media Expert II reached 97.8%, categorized as very valid. The practicality assessment achieved a 95.2% score, deemed very practical. The teacher effectiveness evaluation demonstrated a 90% score, labeled very effective, while the student effectiveness score was 91.9%, also rated very effective. Based on these results regarding validity, practicality, and effectiveness, it can be concluded that the developed adventure game is suitable for use in Informatics education.